Chemical and oxidizable fractions of soil organic matter under different management systems in an Oxisol - Rosset, Jean Sérgio; Lana, Maria do Carmo; Pereira, Marcos Gervasio; Schiavo, Jolimar Antonio; Rampim, Leandro; Sarto, Marcos Vinicius Mansano (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate soil quality from soil organic matter (SOM) chemical and oxidizable fractions in areas with different management systems. The study was carried out in the municipality of Guaira, in the west of the state of the Paraná, Brazil, in areas with different adoption times of the no-tillage system (NT; 6, 14, and 22 years), with succession scheme of soybean (summer) and corn/wheat (winter) crops, besides areas with 12 years under NT – in the same succession scheme – plus four years of Urochloa ruziziensis intercropped with maize (M+U), and with pasture and native forest. The chemical fractions of fulvic acid (FA), humic acid (HA), and humin (HUM) were evaluated, as well as the oxidizable fractions of MOS (F1, F2, F3, and F4), total carbon (TC), and carbon storage (C) in the humic fractions. Total carbon contents increased with the increasing adoption of time of SPD, especially from NT6 to NT22. Humin fraction predominance was observed, with movement of HA and FA in the 0.0–0.4 m soil depth. The oxidizable C fractions showed equilibrium in the distribution of C contents, with higher levels in the more labile fractions, at surface. The cultivation with succession of crops contributes to the increase in labile fractions, but not to the increase of the more recalcitrant fractions of C.